Regulation of chloroplast protein import through a protochlorophyllide-responsive transit peptide - Reinbothe, Christiane (The National Academy of Sciences of the USA, 1997)
NADPH:protochlorophyllide (Pchlide) oxidoreductase (POR) is the key enzyme of chlorophyll biosynthesis in angiosperms. In barley, two POR enzymes, termed PORA and PORB, exist. Both are nucleus-encoded plastid proteins that must be imported posttranslationally from the cytosol. Whereas the import of the precursor of PORA, pPORA, previously has been shown to depend on Pchlide, the import of pPORB occurred constitutively. To study this striking difference, chimeric precursor proteins were constructed in which the transit sequences of the pPORA and pPORB were exchanged and fused to either their cognate polypeptides or to a cytosolic dihydrofolate reductase (DHFR) reporter protein of mouse. As shown here, the transit peptide of the pPORA (transA) conferred the Pchlide requirement of import onto both the mature PORB and the DHFR. By contrast, the transit peptide of the pPORB directed the reporter protein into both chloroplasts that contained or lacked translocation-active Pchlide. In vitro binding studies further demonstrated that the transit peptide of the pPORA, but not of the pPORB, is able to bind Pchlide. We conclude that the import of the authentic pPORA and that of the transA-PORB and transA-DHFR fusion proteins is regulated by a direct transit peptide-Pchlide interaction, which is likely to occur in the plastid envelope, a major site of porphyrin biosynthesis.